Comparative membrane proteomics analyses of breast cancer cell lines to understand the molecular mechanism of breast cancer brain metastasis. Issue 17 (5th July 2017) - Peng, Wenjing; Zhang, Yu; Zhu, Rui; Mechref, Yehia
Abstract: Breast cancer is the leading type of cancer in women. Breast cancer brain metastasis is currently considered an issue of concern among breast cancer patients. Membrane proteins play important roles in breast cancer brain metastasis, involving cell adhesion and penetration of blood–brain barrier. To understand the mechanism of breast cancer brain metastasis, liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) was employed in conjunction with enrichment of membrane proteins to analyze the proteomes from five different breast cancer and a brain cancer cell lines. Quantitative proteomic data of all cell lines were compared with MDA‐MB‐231BR which is a brain seeking breast cancer cell line, thus representing brain metastasis characteristics. Label‐free proteomics of the six cell lines facilitates the identification of 1238 proteins and the quantification of 899 proteins of which more than 70% were membrane proteins. Unsupervised principal component analysis (PCA) of the label‐free proteomics data resulted in a distinct clustering of cell lines, suggesting quantitative differences in the expression of several proteins among the different cell lines. Unique protein expressions in 231BR were observed for 28 proteins. The up‐regulation of STAU1, AT1B3, NPM1, hnRNP Q, and hnRNP K and the down‐regulation of TUBB4B and TUBB5 were noted in 231BR relative to 231 (precursor cell lines from which 231BR is derived). These proteins might contribute to the breast cancer brain metastasis. Ingenuity pathway analysis (IPA) supported the great brain metastatic propensity of 231BR and suggested the importance of the up‐regulation of integrin proteins and down‐regulation of EPHA2 in brain metastasis.